Plastic and locally adapted phenology in cambial seasonality and production of xylem and phloem cells in Picea abies from temperate environments - Gričar, Jožica; Prislan, Peter; Gryc, Vladimír; Vavrčík, Hanuš; de Luis, Martin; Cufar, Katarina (Tree physiology, 2014)
Despite its major economic importance and the vulnerability of Picea abies (L.) H. Karst. to climate change, how its radial growth at intra-annual resolution is influenced by weather conditions in forest stands with a high production capacity has scarcely been explored. Between 2009 and 2011, phenological variation in seasonal cambial cell production (CP) was analysed in adult P. abies trees from three contrasting sites, differing in altitude and latitude. The results indicate that the timing of cambial CP is a highly synchronic process within populations since in all cases the cambium simultaneously started and stopped producing xylem and phloem cells. Our results also demonstrate that the phenology of cambial CP is highly variable and plastic between years, depending on seasonal temperature and precipitation variation. Differences among sites, however, are only partially explained by different environmental (elevation and altitude) and climatic conditions, suggesting that local adaptation may also play a decisive role in the strategy of P. abies for adapting wood and phloem increments to function optimally under local conditions.
Keywords: teplota; Climate; podnebí; Altitude; Trees; floém; Forests; klimatické změny; Xylem; roční období; životní prostředí; xylém; Climate Change; stromy; Rain; Environment; Wood; nadmořská výška; fyziologická adaptace; Phloem; Picea; dřevo; Seasons; déšť; lesy; kambium; smrk; Adaptation, Physiological; Cambium; Temperature